1982
DOI: 10.3382/ps.0610575
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Changes During the Reproductive Period in Four Strains of Turkey Hens

Abstract: Body weight changes were taken at eight times during a 180-day reproductive period in four lines of turkey hens differing by up to 32% in body weight and 82% in egg production. The same pattern of change in body weights was observed in all four lines, indicating that body weight changes during reproduction in turkey hens are not associated with mature body weights or egg production potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…This has been noted previously by Bacon and Nestor (1982) and Siopes (1984). For example, B hens had the same absolute weight (Table 1) as H but less than N yet produced more eggs per hen than either.…”
Section: Days Of Ovipositionsupporting
confidence: 56%
See 2 more Smart Citations
“…This has been noted previously by Bacon and Nestor (1982) and Siopes (1984). For example, B hens had the same absolute weight (Table 1) as H but less than N yet produced more eggs per hen than either.…”
Section: Days Of Ovipositionsupporting
confidence: 56%
“…ously, but Bacon and Nestor (1982) reported that greatly different strains of noncommercial turkey hens have the same pattern of change in absolute BW during the lst-yr of lay. It has been amply noted that BW changes occur (up or down) during the first and second lay periods in turkey hens and that there exists an inverse relation of BW to environmental temperature .…”
Section: Days Of Ovipositionmentioning
confidence: 96%
See 1 more Smart Citation
“…First cycle turkey hens fed ad libitum have been reported to either lose or gain body weight depending on environmental changes, with high environmental temperatures associated witii body weight loss and poor egg production and low environmental temperature associated witii body weight gain during the egg production period (Bacon and Nestor, 1982). Robel (1984) reported a decline in body weight for Large and Small White turkey breeder hens kept in floor pens or cages for a 23-wk egg production period.…”
Section: Discussionmentioning
confidence: 98%